The adaptation of Bem Sex-Role Inventory to respondents from primary school by rephrasing (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
Text, instruction and diagnostic procedure of Ukrainian version of Bem Sex-Role Inventory adapted by the authors for respondents from primary school are presented in the article. Considering the features of psychical development of primary scholars, authors rephrased sixty points submitted in BSRI to involve examinee’s imaginative thinking and to neutralize some semantic mistakes related to figurative mean of a word, its polysemy, belonging to scientific lexicon or borrowing.
Keywords: sex role; Bem Sex-Role Inventory; masculinity; femininity; manhood; womanhood